A Novel Design of Aircraft Fuel Tank Inspection Robot - Guochen Niu; Zunchao Zheng; Qingji Gao; Weijuan Wang; Lei Wang (Institute of Advanced Engineering and Science, 2013)
Aircraft fuel tank leakage is a very common maintenance problem. A continuum robot is designed for troubleshooting of leaks for fuel tank which has strong constraints and is also explosive. The biomimetic robot with several flexible sections applies actuation redundancy through pulling its four independent driving cables to realize bending motion of two degrees of freedom (DOF). The forward kinematics about the relations of cables lengths, angles and tip coordinates of single section is established using projection curvature method and coordinates transformation method. The decoupled multi-section kinematics function is deduced based on the kinematics analysis of single section. Simulations of single section motion are presented. We demonstrate finally the correctness of kinematics method through prototype experiments. DOI: http://dx.doi.org/10.11591/telkomnika.v11i7.2814